Very married : field notes on love & fidelity - Pershey, Katherine Willis (Herald Press, 2016)
Katherine Willis Pershey has never slept with the mailman or kissed an ex-boyfriend. Good thing, since she's married. But simply not committing adultery does not give you the keys to "happily ever after," as Pershey has come to find out in her own marriage and in her work as a pastor. What is this sacred covenant that binds one person to another, and what elements of faith and fidelity sustain it? In Very Married: Field Notes on Love and Fidelity, Pershey opens the book on all things marital. With equal parts humor and intelligence, Pershey speaks frankly about the challenges and consolations of modern marriage. As she shares her own tales of bliss and blunder, temptation and deliverance, Pershey invites readers to commit once again to the joyful and difficult work of cherishing another person. For better or worse. For life. (Publisher)